Participation of non-industrial private forest owners in National Forest Programmes: a discrete choice model for Northern Portugal - Mendes, Américo (2007)
In countries where private forest ownership is very important, knowledge of the behaviour of private forest owners is useful for the design and implementation of successful forest policies. This applies to Portugal where 86 % of the forest lands are private property. This paper presents a study carried out in a region of the Northern part of the country covered by a local forest owners’ association. Based on individual data about the members of this association concerning some of their characteristics (implementation of publicly subsidised afforestation projects, size of the forest holdings, number of forest holdings belonging to the same owner and distance between the permanent residence of the owner and his forest holdings), a multinomial logit model is estimated for the probabilities of participation on public incentive schemes to finance individual and grouped afforestation projects.